Usefulness of echocardiography to detect cardiac involvement in COVID‐19 patients - Cameli, Matteo (Echocardiography, 2020)
Coronavirus disease 2019 (COVID‐19) outbreak is a current global healthcare burden, leading to the life‐threatening severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). However, evidence showed that, even if the prevalence of COVID‐19 damage consists in pulmonary lesions and symptoms, it could also affect other organs, such as heart, liver, and spleen. Particularly, some infected patients refer to the emergency department for cardiovascular symptoms, and around 10% of COVID‐19 victims had finally developed heart injury. Therefore, the use of echocardiography, according to the safety local protocols and ensuring the use of personal protective equipment, could be useful firstly to discriminate between primary cardiac disease or COVID‐19–related myocardial damage, and then for assessing and monitoring COVID‐19 cardiovascular complications: acute myocarditis and arrhythmias, acute heart failure, sepsis‐induced myocardial impairment, and right ventricular failure derived from treatment with high‐pressure mechanical ventilation. The present review aims to enlighten the applications of transthoracic echocardiography for the diagnostic and therapeutic management of myocardial damage in COVID‐19 patients.